Terminograpic Criticism: Structural subdivisions and the terminological field of metalanguage - Oleksijivna Petrova, Tetjana (Slavia Centralis, 2021)
The article deals with the structure of terminographic criticism as an independent scientific direction. It is found that terminographic criticism is a hierarchically systematised subject area which integrates two sections: 1) the theory and history of terminographic criticism, 2) the practice of terminographic criticism. Terminographic criticism closely interacts with different sciences and is formed on the basis of the system of their qualitative knowledge. The simulated structure of the metalanguage terminological field of the terminographic critisism proves the formation of its conceptual apparatus. The following levels define its terminological field: the macrofield is "the terminographic criticism", which is organised by two terminological microfields – "the theory and history of terminographic criticism" and "the practice of terminographic criticism" which constitute correspondent terminological and semantic groups. The conceptual core of the terminological field of the metalanguage terminographic criticism is formed by its basic terms.
Keywords: term; terminographic criticism; terminological field; macrofield; microfield; terminological and semantic group